Hyperendemic clone of KPC producing Klebsiella pneumoniae ST 258 in Buenos Aires hospitals - Cejas, Daniela (2012)
Since KPC-type carbapenemases were first reported in Klebsiella pneumoniae in 2001 in the USA , they have become a frequent resistant marker encountered also in other Enterobacteriaceae and Pseudomonads from the Americas, Europe, Asia and Middle East. Their wide spread across multiple continents and species has been associated with a mobile genetic element, Tn4401. More recently, the molecular epidemiology of KPC producing K. pneumoniae isolates has revealed the successful dissemination of a single sequence type 258 clone. Although in Argentina KPC-2 producing K. pneumonia were first detected in 2006 a substantial increase was observed in 2010, in Buenos Aires To characterize this occurrence, single, non-repetitive K. pneumonia isolates obtained from 57 patients from May 2009 through april 2010 in six hospitals in Buenos Aires were included. Antimicrobial susceptibility tests were conducted by disk diffusion according to CLSI recommendations. An enhancement in the inhibition zone of the carbapenem containing disks adjacent to the one containing the inhibitor was considered a positive screening for KPC. All the isolates displayed The presence of blaKPC was confirmed by PCR amplification As the XbaI PFGE patterns generated were indistinguishable , multilocus sequence typing (MLST) with seven housekeeping genes was performed on selected isolates representing the different hospitals, corresponding to ST258 The spread of KPC-producing clones constitutes a serious infection control concern. Prevention of their dissemination requires prompt, accurate and proactive laboratory detection systems followedby strong reinforcement of contact isolation precautions and hygiene measures. The outbreak was able to be easily controlled only at hospital 1 where the suspicious index case was detected and informed from the preliminary antibiotic tests, performed as mentioned previously. Control measurements were applied on these preliminary data, even before genetic confirmation.